1995
DOI: 10.1002/pd.1970150609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maternal serum alpha‐fetoprotein and free beta human chorionic gonadotrophin in the first trimester: Implications for down's syndrome screening

Abstract: The aim of this study was to determine the maternal population, pregnancy, serum alpha-fetoprotein (AFP) and free beta subunit of human chorionic gonadotrophin (F beta hCG) parameters in a large series of women attending prenatal clinics before 15 weeks' gestation and to assess the practical problems of population screening for Down's syndrome in the first trimester using these markers. Serum samples were collected from 8600 women attending prenatal clinic booking visits. Maternal serum AFP and F beta hCG medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
11
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
7
11
0
Order By: Relevance
“…What data there are suggests that free b-hCG may be elevated to about twice normal. Berry et al (1995) showed median levels of 1.97 MoM in 50 sets of twins and Noble et al (1997) similarly found median levels of 1.94 MoM in 136 sets of twins. Brambati et al (1997) also showed a median of 1.94 in 35 dichorionic and 4 monochorionic twin pregnancies.…”
Section: Discussionsupporting
confidence: 57%
“…What data there are suggests that free b-hCG may be elevated to about twice normal. Berry et al (1995) showed median levels of 1.97 MoM in 50 sets of twins and Noble et al (1997) similarly found median levels of 1.94 MoM in 136 sets of twins. Brambati et al (1997) also showed a median of 1.94 in 35 dichorionic and 4 monochorionic twin pregnancies.…”
Section: Discussionsupporting
confidence: 57%
“…We used the measured population parameters for the urine markers, published normal parameters for serum free beta hCG (Berry et al, 1995) with data for Down's pregnancies ascertained from a meta analysis (Cuckle, 1996) of 340 cases from the world's literature (unpublished data, Spencer, 1996), and data on nuchal translucency from the combined King's College studies (unpublished data, Nicolaides et al, 1996). Using these population parameters, a series of random MOM values or delta nuchal translucency values (Pandya et al, 1995) were selected from within the distributions of the affected and unaffected populations for each analyte.…”
Section: Methodsmentioning
confidence: 99%
“…␣-Fetoprotein (AFP) and ␤-human chorionic gonadotropin (hCG␤) are important tumor markers and also serve as aids in prenatal detection of fetal malformations (25)(26)(27)(28). Numerous immunologic methods for determining AFP and hCG␤ concentrations have been described (29 -35 ), but few methods other than time-resolved immunofluorometric assays and enzyme immunoassays can measure them simultaneously (28,36,37 The coating buffer was 100 mmol/L sodium carbonate buffer (pH 9.5) containing 9 g/L NaCl and 0.…”
mentioning
confidence: 99%